2008
DOI: 10.1021/jf800158p
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Nonstructural Carbohydrates of Mezcal Agave (Agave salmiana Otto ex Salm-Dick)

Abstract: Fructans are the reserve carbohydrates in Agave spp. plants. In mezcal factories, fructans undergoes thermal hydrolysis to release fructose and glucose, which are the basis to produce this spirit. Carbohydrate content determines the yield of the final product, which depends on plant organ, ripeness stage, and thermal hydrolysis. Thus, a qualitative and quantitative characterization of nonstructural carbohydrates was conducted in raw and hydrolyzed juices extracted from Agave salmiana stems and leaves under thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 24 publications
(31 reference statements)
0
50
0
4
Order By: Relevance
“…16 Most of the recent research on the agave stem and sap has been focused on fructan analysis. 11,13,15,17,18 A previous study reported that aguamiel from A. mapisaga contained 11.5% of dry matter, mainly composed of sugars (75%; among them, 10% fructans. 15 Agave has also been studied with regard to its health properties as a food or plant extract related to certain secondary metabolites.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Most of the recent research on the agave stem and sap has been focused on fructan analysis. 11,13,15,17,18 A previous study reported that aguamiel from A. mapisaga contained 11.5% of dry matter, mainly composed of sugars (75%; among them, 10% fructans. 15 Agave has also been studied with regard to its health properties as a food or plant extract related to certain secondary metabolites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When the agave enters the reproductive stage, its shoot apex is thinned, displaying black, shiny spines. 11 Agaves were prepared following the traditional process to collect the aguamiel. 14 Aguamiel was collected during the month of May 2013.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is due to the fact that with most fructans and dry matter content are found in the stem (Aguirre et al, 2001;Michel-Cuello et al, 2008), and when processing the entire head a dilution effect happens with the highest humidity of the stalk bases. The tertiary juice presented between 5.4 and 7.2 °Bx which mainly corresponds to remaining fructans, recovered with the washing and pressing of the bagasse.…”
Section: Extracción De Fructanosmentioning
confidence: 99%
“…It is fundamental to acknowledge the vegetative to reproductive change, known as quiotillo stage in the highlands of San Luis Potosí, for the rational use of the maguey (Aguirre et al, 2001). Another very important factor for the quality of the fructans is if the entire head of the maguey is used (comprised by the stem and the bases of the leaves) as raw material, instead of only the stem, the organ of the plant where the reserve substances are accumulated (Michel-Cuello, Juárez-Flores, Aguirre-Rivera, & Pinos-Rodríguez, 2008). When the entire head is processed as has been the appropriate procedure for other purposes, it requires more complex and expensive operations to eliminate other existing compounds at the base of the leaves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation